2020
DOI: 10.1101/2020.05.22.111187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-determined expression of priming protease TMPRSS2 and localization of SARS-CoV-2 infection in the lung epithelium

Abstract: The emergence of the SARS-CoV-2 novel coronavirus has led to a global pandemic , with more than 5 million cases as of May 2020 1 . Available data suggest that severe illness and death from COVID-19 are rare in the pediatric population 2 . Integrating single-cell RNA sequencing of the developing mouse lung with temporally-resolved RNA-in-situ hybridization (ISH) in mouse and human lung tissue, we found expression of SARS-CoV-2 Spike protein primer TMPRSS2 was highest in ciliated cells and type I alveolar epithe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(43 reference statements)
2
18
0
Order By: Relevance
“…Nevertheless, TMPRSS2 gene expression data from the GTEx database do not highlight any difference between males and females. Importantly, developmental regulation of the expression of the TMPRSS2 gene has been suggested that may underlie the relative protection of infants and children from severe respiratory illness (Schuler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, TMPRSS2 gene expression data from the GTEx database do not highlight any difference between males and females. Importantly, developmental regulation of the expression of the TMPRSS2 gene has been suggested that may underlie the relative protection of infants and children from severe respiratory illness (Schuler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS2 is highly expressed in ileal absorptive enterocytes, nasal goblet secretory cells, epithelial cells of bronchi, as well as type I and type II alveolar cells (Bertram et al, 2012;Collin et al, 2020;Ziegler et al, 2020). TMPRSS2 expression in type I alveolar cells increases with aging in mice and humans (Schuler et al, 2020). Additionally, TMPRSS2 is highly expressed in corneal epithelium and conjunctival specimens, suggesting that ocular surface cells could be the gateway of SARS-CoV-2 as well as a reservoir for personto-person transmission (Collin et al, 2020).…”
Section: Tissue Expression Of Tmprss2 Genementioning
confidence: 99%
“…In addition, oncogenic roles of TMPRSS2 may be linked to poor outcomes with COVID-19 as well [16], which should be studied in the future. Using single-cell RNA-sequencing analysis, Schuler et al showed that TMPRSS2 expression was highest in ciliated cells and type I alveolar epithelial cells (AT1) and increased with aging in humans and mice [17]. This (See figure on previous page.)…”
Section: Tmprss2 Polymorphism Analysis Across Different Populationsmentioning
confidence: 99%
“…In the same contest, Hou et al found that, the p. Asp435Tyr which is a key site for catalytic residue binding of TMPRSS2 has unique low-frequency allele, but predominant SNPs in TMPRSS2 and offer possible descriptions for differential genetic infectivity to COVID-19 and for risk influences, such as those with tumor and male patients. By using the analysis of single-cell RNA-seq, Schuler et al revealed that the expression of TMPRSS2 was upregulated in ciliated cells and alveolar epithelial type 1 cells and increased with humans aging [94]. This observation indicates that the developmental TMPRSS2 expression regulation may have a role in the relative protection of the children and infants from COVID-19 infection.…”
Section: Tmprss2 Polymorphism Analysis With Covid-19 Diseasementioning
confidence: 99%